Native Huts of Trinidad, B.W.I. - (:unkn) unknown (Matthews Art Service, New York, 2010)
The postcard shows two East Indian women, one is doing the laundry and the other might be her daughter. To the left of the women, a little boy is taking a bucket bath. In the background are huts with thatched roofs. Postcard number 793.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Huts--Trinidad and Tobago; Dwellings--Trinidad and Tobago; East Indians--Trinidad and Tobago; Rural families--Trinidad and Tobago; Children--Trinidad and Tobago; Housing, Rural--Trinidad and Tobago; Thatched roofs--Trinidad and Tobago; Communities--Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Families--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Ajoupa